2013
DOI: 10.1002/jssc.201200851
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of seven lignans in Justicia procumbens by high performance liquid chromatography–photodiode array detection using relative response factors

Abstract: A simple and sensitive HPLC coupled with photodiode array (HPLC-PDA) method was developed for simultaneous determination of seven lignans in Justicia procumbens using relative response factors (RRFs). The chromatographic separation was performed on a Shiseido Capcell Pak C(18) column (250 × 4.6 mm id, 5 μm), a gradient elution of acetonitrile/water, and a photodiode array detector. The column temperature was maintained at 35°C and the detection wavelength was set at 256 nm. Chinensinaphthol methyl ether was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
0
15
1
Order By: Relevance
“…Previous study showed that the content of HJC in J. procumbens was lower than those in JB, CME, HJB, and HJA (24). However, our research showed that the IC 50 of HJC on K562 and HL-60 cell lines was lower than that of HJA (Fig.…”
Section: Discussioncontrasting
confidence: 53%
“…Previous study showed that the content of HJC in J. procumbens was lower than those in JB, CME, HJB, and HJA (24). However, our research showed that the IC 50 of HJC on K562 and HL-60 cell lines was lower than that of HJA (Fig.…”
Section: Discussioncontrasting
confidence: 53%
“…The application of this UHPLC method significantly shortened the analysis time. All arylnaphthalene lignans were successfully separated within 13 min (14–18 min was set as posttime) and showed higher efficiency as well as less solvent consumption than previous studies .…”
Section: Resultsmentioning
confidence: 84%
“…In addition, we have isolated five arylnaphthalene lignans from J. procumbens including HJA, 6′-hydroxy justicidin B (HJB), justicidin B (JB), CME and Taiwanin E methyl ether (TEME) [28], [29] and demonstrated that these are the main arylnaphthalene lignans in J. procumbens [30]. Notably, these compounds share the same parent nucleus but harbor different substituent groups at the 1, 3′, 4′ and 6′ positions.…”
Section: Introductionmentioning
confidence: 99%